A combination of check tug and fascial interposition with no-scalpel vasectomy. Issue 2 (1st April 2001) - Kumar, Vivek; Kaza, Ramchandra M
Abstract : The prospective study was carried out to evaluate the success rates of combining a check tug and fascial interposition while performing a no-scalpel vasectomy. A total of 2150 male acceptors visiting the family welfare clinic of Lok Nayak Hospital, Delhi, from July 1992 to June 1995 and opting for a no-scalpel vasectomy, underwent a combination of check tug and fascial interposition during the procedure. These men were followed-up for failure rates as shown by semen analysis, 3 months and at least 20 ejaculations following the procedure. All the clients showed a negative sperm count during the subsequent follow-up, less than two non-motile sperms per high power field being taken as a negative count (n = 5) and there were no reported pregnancies. A check tug ensures that the same vas deferens is not ligated twice, particularly as the approach is a midline one. The fascial interposition prevents spontaneous recanalisation of the cut vas. Thus the combination of the two would further increase the reliability of the procedure.